2018
DOI: 10.1063/1.5011392
|View full text |Cite
|
Sign up to set email alerts
|

Field-effect transistors as electrically controllable nonlinear rectifiers for the characterization of terahertz pulses

Abstract: We propose to exploit rectification in field-effect transistors as an electrically controllable higher-order nonlinear phenomenon for the convenient monitoring of the temporal characteristics of THz pulses, for example, by autocorrelation measurements. This option arises because of the existence of a gate-bias-controlled super-linear response at sub-threshold operation conditions when the devices are subjected to THz radiation. We present measurements for different antenna-coupled transistor-based THz detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…On the contrary, a large number of publications have reported measurements on THz rectification by MOS-FET [1,[19][20][21][22][23] using the drain (sometimes the source) as the detection port, with the source (drain) electrode grounded. In such cases, the structure is 2D, and in principle a comparison with the 1D model should not be possible.…”
Section: Discussion Of a Prospective 2d Modelmentioning
confidence: 99%
“…On the contrary, a large number of publications have reported measurements on THz rectification by MOS-FET [1,[19][20][21][22][23] using the drain (sometimes the source) as the detection port, with the source (drain) electrode grounded. In such cases, the structure is 2D, and in principle a comparison with the 1D model should not be possible.…”
Section: Discussion Of a Prospective 2d Modelmentioning
confidence: 99%
“…Recent experiments [ 6 , 35 ] have demonstrated that different FETs, such as Si MOSFETs (metal-oxide-semiconductor field-effect transistor) and AlGaN/GaN HEMTs (high-electron-mobility transistor) at the sub-threshold gate bias, when illuminated by a short-pulse of THz radiation, also exhibit a super-linear response slope before reaching saturation. In this regime, the voltage signal of the transistor is proportional to the radiation power as , where the index n is greater than 1.…”
Section: Si Cmos Fet Detectormentioning
confidence: 99%
“…In addition, antenna-coupled field-effect transistors (FET) and the Schottky diodes have recently emerged as useful devices for room-temperature THz autocorrelators [ 4 , 5 ]. We have recently demonstrated that FETs biased in the sub-threshold regime in a certain range of excitation amplitudes exhibit a super-linear response [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…THz radiation came into play to derive information from both the spectral response of the molecules and from the changes of the conductivity of the VACNTs. In addition, long-term developments of THz detectors based on antenna-coupled field-effect transistors (Ter-aFETs) by Lisauskas et al [147] had led to the investigation of such THz devices which were optimized in various material sys-tems including Si complementary metal-oxide semiconductor (CMOS) platforms, [147] AlGaN/GaN [148] and graphene. [149] Moreover, power detection and heterodyne operation with single detectors and multipixel arrays were recently explored, and a number of applications studied.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…[149] Moreover, power detection and heterodyne operation with single detectors and multipixel arrays were recently explored, and a number of applications studied. [148] Earlier, Lisauskas et al investigated the interplay of two detection mechanisms using the example of graphene TeraFETs, that is, the Dyakonov-Shur mechanism (the high-frequency extension of classical resistive mixing [147] ) and the hot-carrier photothermal effect (diffusive contribution resulting from the heating of the charge carriers by the THz wave), which is especially strong in graphene and carbon nanotubes. Understandably, to make these THz devices perform well, such interplay must be carefully adjusted.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%